The role of interior design elements in enhancing privacy in the traditional Arab house (the traditional Mosul house as a model) (Journal of Planner and Development, 2025)
The traditional house reflects significant social and cultural significance. It represents a reflection of Arab heritage and family values, highlighting the continuity of heritage in the face of natural challenges, as it is influenced by environmental, heritage, and social factors. As a result of adherence to Islamic principles and consideration of the local climate, customs, and traditions, private spaces are designed for families, with an emphasis on privacy for women, especially in traditional residential design. Residential units constitute the largest amount of the total construction production in the Arab city, and are considered one of the strong influences on the internal environmental data that contradict with the external environment of the house. Therefore, the current study aims to highlight the importance of the architectural elements in the traditional heritage house that affect privacy and distinguish it with a special identity represented by the use of architectural elements that are appropriate to the environmental and social requirements of Arab society. The research methodology relied on designing a special questionnaire and the study samples were residents of traditional houses in the old city of Mosul. The method of observation and formal analysis of selected samples was adopted to explore the design characteristics that enhance visual privacy. It was found that privacy is of great importance when residents choose their homes, followed by the residential region, then the residential area and type, and finally its spatial organization. The elements of the interior design of Mosul houses are affected by (92.5%) the value of privacy, which contributes to creating a unique residential environment and a distinctive architectural identity for the region. This is achieved by using architectural elements, the most prominent of which are (the indirect entrance, the mashrabiya, the iwan, the corridors, the private rooms, and the high roof curtain). A multiple linear regression was also carried out using the SPSS program, and its results showed that the design of the entrances in the heritage houses has a significant positive impact on privacy, while the internal spaces showed a negative impact. As for the openings (windows and internal doors), their impact was slightly positive, and finally, the furniture had a somewhat negative impact.